Investigation and prediction of fatigue performance of SLM 316 L stainless steel based on small build orientation variations and heat treatment effects - Andrei Yankin; Asma Perveen; Didier Talamona (Scientific Reports)
Abstract Additive manufacturing (3D printing) has facilitated the creation of complex structures, including lattices with diverse build angles. Since lattices often face quasi-static and cyclic loads, understanding material properties across a wide range of printing angles, post-processing conditions, and loading scenarios is crucial. This study explores the effects of building orientations beyond conventional 0, 45, and 90 degrees on the mechanical properties of 316 L steel, produced by laser powder bed fusion. Quasi-static and cyclic tensile tests were performed to evaluate mechanical behavior in as-built and heat-treated conditions, followed by predictive model development. The ultimate strength showed a modest variation of 7% in the as-built condition, while the heat-treated state exhibited a greater variation of 13%. Fatigue tests indicated minor differences between conditions in the low-cycle region but larger gaps in the high-cycle region, where heat-treated samples generally showed superior performance. Inclination angle had a greater effect on fatigue life in the as-built state, with horizontal part orientations outperforming vertical ones. The predictive model demonstrated robust reliability, with nearly 90% of data within an accepted scatter factor of less than three. Requiring minimal experimental data (two fatigue curves per condition), the model is valuable for forecasting fatigue behavior in complex lattice structures.